Dinamika Keterlibatan Sosial Teman Sebaya dalam Pembelajaran Akademik Siswa Sekolah Menengah Atas - Didit Darmawan; Antok Widodo (Jurnal Al-Fatih, 2026)
Social engagement with peers in academic contexts represents a fundamental dimension of learning experiences among senior secondary school students, encompassing cognitive collaboration, emotional support, and the co-construction of knowledge within peer networks. This qualitative literature review explores how academic peer engagement is experienced and interpreted by students at the upper secondary level, synthesizing theoretical perspectives from educational psychology and sociocultural learning theories. The investigation reveals that academic peer engagement manifests through diverse forms ranging from informal conversations to structured study groups, with quality influenced by personal factors such as self confidence and communication skills, relational factors including trust and reciprocity, and structural factors involving classroom design and instructional methods. Power dynamics and social status within peer groups shape differential access to academic resources, while students construct varied meanings from their engagement experiences, interpreting them as expressions of solidarity, pragmatic learning strategies, or sources of social pressure. The impact on academic achievement proves complex, with optimal conditions fostering conceptual understanding through knowledge co construction, while suboptimal conditions risk fostering dependency or inequitable participation. Educators play a crucial moderating role through intentional facilitation of collaborative activities, and cultural values alongside digital environments significantly shape engagement patterns. The study contributes to understanding academic peer engagement as a dynamic process requiring systematic support to realize its potential as a valuable educational resource.